Secular trends and sociodemographic determinants of thinness, overweight and obesity among Chinese children and adolescents aged 7–18 years from 2010 to 2018 - Li, Chengyue; Zhang, Mingxuan; Tarken, Alimujiang Yimiti; Cao, Yuping; Li, Qian; Wang, Hao (Frontiers in Public Health, 2023)
Background: Most studies have focused on overweight/obesity and its secular trend, with insufficient studies on the factors influencing thinness and trends recently. To examine the trends of prevalence and sociodemographic determinants of thinness, overweight, and obesity among Chinese children and adolescents aged 7 to 18 years from 2010 to 2018. Methods: This study was based on cross-sectional data of 11,234 children and adolescents aged 7 to 18 years from the Chinese Family Panel Studies (CFPS) in 2010, 2014 and 2018, including anthropometric and sociodemographic characteristics variables. The nutritional status of each individual was determined according to China and WHO criteria. The demographic characteristics of different subgroups were tested by chi-square, and log-binomial regression was used to analyze the trend of prevalence and the relationship between sociodemographic characteristics and different nutritional statuses. Results: After adjusting for age, from 2010 to 2018, the overall prevalence of thinness decreased, and the prevalence of overweight increased in Chinese children and adolescents. The overall prevalence of obesity declined in boys and increased in girls, but in adolescents aged 16-18 years, it increased significantly. Log-binomial regression analysis showed that among all subjects, time (years), 16-18 years were negatively associated with thinness, while 13-15 years, walking to school, large family size, and paternal age at childbirth older than 30 years old were positively associated with thinness; 10-12/13-15/16-18 years, boarding at school, medium and large family sizes, and mother's education at junior middle school/junior high school and above were negatively associated with overweight/obesity, while time (years), boys were positively associated with overweight/obesity in the multivariate model by adjusting for the statistically significant factors (all p < 0.05). Conclusion: Chinese children and adolescents are facing a double burden of malnutrition. Future public health policies and interventions should prioritize high-risk groups specifically young age groups, boys, larger family sizes and so on.